PATRIARCHAL IDEOLOGY AND GENDERED AUTHORITY IN BUGIS PAPPASENG: A CRITICAL DISCOURSE ANALYSIS OF CLASSICAL TEXTS - Syamsudduha Syamsudduha; Andi Muhammad Irawan; Sultan Sultan (Jurnal Gramatika, 2026)
Gender inequality and patriarchal social order continue to shape many contemporary societies, often rooted in long-standing cultural texts that are rarely questioned critically. In Bugis society, pappaseng, classical advisory texts transmitted across generations, are widely regarded as sources of moral guidance and social values. However, limited scholarly attention has been given to how these texts discursively construct and legitimize gendered power relations. Addressing this gap, this study investigates how patriarchal ideology and gendered authority are embedded and normalized in Bugis pappaseng. Drawing on Critical Discourse Analysis (CDA), particularly van Dijk’s socio-cognitive framework and the ideological square of self- and other-presentation, this study analyses eleven selected pappaseng excerpts that explicitly or implicitly articulate gender roles, moral expectations, and social authority. The analysis reveals two dominant discourse constructions: the discourse of the ideal woman and the discourse of male domination. Women are represented as morally regulated subjects whose social value is defined by obedience, restraint, and their role in maintaining siri’ (honour and shame), whereas men are constructed as legitimate authority holders associated with leadership, control, and public power. Through polarized discursive strategies, pappaseng texts naturalize and moralize patriarchal relations, presenting gender hierarchy as culturally appropriate and divinely sanctioned. This study argues that pappaseng functions not only as cultural wisdom but also as an ideological apparatus that reproduces gender inequality over time. By focusing on classical texts, this research extends feminist CDA beyond contemporary discourse and underscores the importance of critically re-examining traditional narratives in efforts toward gender justice. Future research is encouraged to explore comparative ethnic texts and alternative or resistant readings within classical discourse traditions.